Nanocarbon-based catalysts for selective nitroaromatic hydrogenation: A mini review - Yao, Jiarong; Wang, Li; Xie, Dong; Jiang, Linxuan; Li, Jiantong; Fang, Xiaomin (Frontiers in Chemistry, 2022)
Selective hydrogenation of nitroaromatics to the corresponding anilines is a key topic for the research in fine chemical industrial fields. Nanocarbon materials with good chemical stability, high electrical conductivity, and mechanical performance have been regarded as promising candidates and shown wide applications in recent years. Controllable synthesis on structure, morphology and active sites of nanocarbon-based catalyst are vital to the development of highly efficient catalysts. In this mini-review, we summarize the recent progresses of nanocarbon materials by focusing on the synthesis approaches and corresponding nanostructures, including carbon nanofibers, carbon nanotubes, graphene, porous carbon, carbon spheres, as well as MOF derived carbon materials. The design and catalytic performance of these nanocarbon materials have been systematically discussed. Finally, the emerging challenges and future prospective for developing advanced nanocarbon based catalysts were outlined.